Avaliação das propriedades mecânicas e elétricas da liga 6201 não refinada, modificada com os teores de cobre (0,05 e 0,3)% para transporte de energia elétrica - VENTURA, Odila da Silva Passos (Universidade Federal do Pará, 2014)
At the present work, experiments were made with the unrefined alloy Al – 0,6%Mg - 0,8%Si, with variations in copper content (0,05% e 0,3%), that aimed to evaluate two aspects of the alloy behavior. The first aspect concerns the affinity between it and the mold, which seeks to observe the effect of the solidification thermal variables of the structure of molten and the correlation with mechanical and electrical properties, the second aspect is related with the intrinsic behavior of the variation on the chemical composition subject at low speed and cooling rates. For evaluating the solidification thermal variables (liquidus isotherms velocities, cooling rates) was used a device for horizontal unidirectional solidification. The ingots produced from the solidification of the alloy rose by mechanical machining, laminating and steel drawing, examined in different positions and diameters, by testing the traction and electric conductivity. Fractures were analyzed in terms of micro cavities and different levels of copper and it was found that in the cold deformed material, the limit of tensile strength has a trend of growth for the alloys of higher concentration of copper. The measured values have also concluded that the electrical conductivity increases the greater the diameter of the micro cavities and lower the copper content. In order to evaluate only the intrinsic variation behavior of the alloy chemical composition, a second device was used for solidification, mold in "U", painted internally in solution of kaolin that attaches to such low rates of cooling. The results show that for both copper content there is a tendency of increase in the limit of tensile strength with increasing reduction suffered by the samples, the limit of tensile strength greater for the alloy with higher copper content. We attach this behavior to the higher content of solute which in turn showed better response to plastic deformation, compressing the material. However, the electrical characterization occurs in an opposite way, as seen in unidirectional solidification, where the lowest copper content was more efficient.